Determination of Residues Responsible for Substrate and Product Specificity of Solanum habrochaites Short-Chain cis-Prenyltransferases . Issue 1 (19th November 2013) - Kang, Jin-Ho; Gonzales-Vigil, Eliana; Matsuba, Yuki; Pichersky, Eran; Barry, Cornelius S.
Abstract : The relative positions of aromatic amino acids and adjacent residues within domain II of short-chain cis-prenyltransferases contributes to the evolution of volatile terpene biosynthesis in Solanum species trichomes . Abstract: Isoprenoids are diverse compounds that have their biosynthetic origin in the initial condensation of isopentenyl diphosphate and dimethylallyl diphosphate to form C10 prenyl diphosphates that can be elongated by the addition of subsequent isopentenyl diphosphate units. These reactions are catalyzed by either cis-prenyltransferases (CPT s) or trans-prenyltransferases. The synthesis of volatile terpenes in plants typically proceeds through either geranyl diphosphate (C10) or trans-farnesyl diphosphate (C15), to yield monoterpenes and sesquiterpenes, respectively. However, terpene biosynthesis in glandular trichomes of tomato ( Solanum lycopersicum ) and related wild relatives also occurs via the cis-substrates neryl diphosphate (NPP ) and 2   Z, 6   Z -farnesyl diphosphate ( Z, Z -FPP ). NPP and Z, Z -FPP are synthesized by neryl diphosphate synthase1 (NDPS1) and Z, Z -farnesyl diphosphate synthase (zFPS), which are encoded by the orthologous CPT1 locus in tomato and Solanum habrochaites, respectively. In this study, comparative sequence analysis of NDPS1 and zFPS enzymes from S. habrochaites accessions that synthesize either monoterpenes or sesquiterpenes was performed to identify amino acid residues that correlate with the ability to synthesize NPP or Z, Z -FPP . Subsequent structural modeling, coupled with site-directed mutagenesis, highlighted the importance of four amino acids located within conserved domain II of CPT enzymes that form part of the second α-helix, for determining substrate and product specificity of these enzymes. In particular, the relative positioning of aromatic amino acid residues at positions 100 and 107 determines the ability of these enzymes to synthesize NPP or Z, Z -FPP . This study provides insight into the biochemical evolution of terpene biosynthesis in the glandular trichomes of Solanum species.